ICT-based Lubuk Oguang and Barangin Waterfall Tourism Development at Pangkalan Indarung Kuantan Singingi - Ismandianto, Ismandianto; Muchid, Muchid; Handoko, Tito; Marta, Auradian; Wicaksono, Luluk Reza (JOURNAL OF COMMUNITY SERVICES PUBLIC AFFAIRS, 2023)
district, Kuantan Singingi Regency is one of the regional tourism development plans contained in the regional medium-term development plan in Regional Regulation No. 1 of 2017. Currently the tourism agency with the existing tourism community includes tourism awareness groups that have begun to take shape including the development of lubuk oguang tourism in Pulau Padang Village and Windy Waterfall in Pangkalan Indarung Village. Community service in collaboration with the Tourism Office and the Singingi Regency Indonesian Enchantment Movement conducted tourism potential development activities based on ICT (Information and Communication Technologies). The stages of dedication by coordinating with tourism service partners are going well according to the proposals and service plans. The activity also involved real work college students (Kukerta) complementing each other.